Educational Counsellor and Challenges in Working withSpecial Needs Students (Raparin Journal of Humanities (RJH), 2026)
This study aims to examine the social challenges faced by educational counsellors in developing the skills of students with disabilities within school settings. The emphasis on this objective arises from the pivotal role that educational guidance plays in supporting and enhancing the abilities of students with disabilities. Despite its significance, the implementation of this role is hindered by a range of challenges, which this research seeks to identify and analyse. Adopting a qualitative research design, the study employed thematic analysis to interpret data collected through in-depth interviews. Findings reveal three main categories of challenges. First, administrative challenges include a limited understanding of the counsellor’s role, inadequate coordination within work teams, insufficient material resources, a lack of financial rights, minimal incentives or recognition, and the absence of professional training opportunities. Second, challenges related to the counsellor’s professional performance, such as low job satisfaction and insufficient experience or expertise. Finally, challenges linked to the families of students with disabilities, encompassing non-acceptance or concealment of the disability, limited awareness and access to information, and students’ resistance to instructions.